Controlling the rainbow lorikeet in Tasmania: is it too late?. (1st October 2020) - Robinson, Susan A.; Baker, G. Barry; Barclay, Candida
ABSTRACT: Throughout the world, many parrot species have established wild populations outside their natural range through accidental escapes and deliberate releases from captivity. The Rainbow Lorikeet ( Trichoglossus moluccanus ), native to coastal northern and eastern continental Australia, has established viable populations in Western Australia and New Zealand from escaped or released pets and more recently have established in Tasmania. The Western Australian experience with introduced Rainbow Lorikeets, clearly shows that significant costs and impacts to agriculture, the environment and human amenities can be expected if this species is not controlled in the early stages of population increase, while in New Zealand, early intervention has proven successful in removing the species from the wild. This study examines sighting records of Rainbow Lorikeets in Tasmania which have gradually established over 20 years and we present a model to assist in determining likely population trajectories under various scenarios of control. Modelling indicates that the removal of 200 birds per year from each of the three Tasmanian sub-populations would decrease numbers to near-zero within 4.6 years. This demonstrates the opportunity to effectively control the Rainbow Lorikeet in Tasmania still exists and substantial damage to agriculture and impacts to conservation values can be avoided, resulting in significant cost savings to the Tasmanian community.